Therapeutic Drug Monitoring and Individualized Medicine of Dasatinib: Focus on Clinical Pharmacokinetics and Pharmacodynamics - He, Shiyu; Bian, Jialu; Shao, Qianhang; Zhang, Ying; Hao, Xu; Luo, Xingxian; Feng, Yufei; Huang, Lin (Frontiers in Pharmacology, 2021)
Dasatinib is an oral second-generation tyrosine kinase inhibitor known to be used widely in Philadelphia chromosome-positive (Ph+) chronic myeloid leukemia (CML) and Ph+ acute lymphoblastic leukemia (ALL). Notably, although a high pharmacokinetic variability in patients and an increased risk of pleural effusion are attendant, fixed dosing remains standard practice. Retrospective studies have suggested that dasatinib exposure may be associated with treatment response (efficacy/safety). Therapeutic drug monitoring (TDM) is gradually becoming a practical tool to achieve the goal of individualized medicine for patients receiving targeted drugs. With the help of TDM, these patients who maintain response while have minimum adverse events may achieve long-term survival. This review summaries current knowledge of the clinical pharmacokinetics variation, exposure-response relationships and analytical method for individualized dosing of dasatinib, in particular with respect to therapeutic drug monitoring. In addition, it highlights the emerging insights into several controversial issues in TDM of dasatinib, with the aim of presenting up-to-date evidence for clinical decision-making and insights for future studies.